MULTICULTURAL ISLAMIC EDUCATION: A CASE STUDY OF RELIGIOUS TOLERANCE AND HARMONY IN KALIMANGGIS VILLAGE, DISTRICT KALORAN, TEMANGGUNG REGENCY - Dinar Bela Ayu Najma; Syamsul Bakri (Balai Penelitian dan Pengembangan Agama Jakarta, 2022)
This paper aims to explain the history of Kalimanggis Village as a multicultural village model of multicultural Islamic education and the role of Muslims in creating tolerance. To achieve this goal, it is necessary to use descriptive qualitative, namely knowing the meaning of the reality under study. This research results (1) The multicultural reality in Kalimanggis Village is a natural fact that has been formed by the social history of the community over a long period of time so that the culture remains solid in the movement of time until now. (2) The model of multicultural Islamic education in Kalimanggis Village is adaptive and compromising on the multicultural culture and local wisdom that exists in the community. (3) Islamic leaders, play religion as social glue in the midst of the diversity of society, to strengthen harmony. This shows that religion has a very strong influence in creating a social reality.